Negative interest rates: how the existent financial models can fit with this new scenario? a focus on vasicek and CIR - Compagnone, Silvia (2018)
My project work has the purpose to question on the use of financial models with this new scenario of negative interest rates. Precisely, the two models I am going to study are the Vasicek and CIR. First of all, the research will be focused on the analysis of them looking at both their limitations and strengths, and trying to make some needed and essential modifications for this shift in macroeconomic scenario. The entire work has the objective of understanding which are the economic agents affected and which are the future perspectives in this economic situation.